Corrigendum to “Does Piroxicam really protect ischemic neurons and influence neuronal firing in cerebral ischemia? An exploration towards therapeutics” [Med Hypotheses 81 (2013) 429–435] (Medical Hypotheses (2013) 81(3) (429–435), (S0306987713002806), (10.1016/j.mehy.2013.06.002)) - Bhattacharya P.; Kumar Pandey A.; Paul S.; Patnaik R. (My University, 2025)
In figure 2 of this article there is a representation of improvement in infract volume in Piroxicam pre-treated vehicle Rats (* vs. sham &** vs. Vehicle) between the different groups by TTC staining. We rectify the previous misuploaded TTC images and provide correct representative TTC images. [Figure presented] The changes has no significant difference in the infarct volume graph and conclusion of the study>. The authors would like to apologise for any inconvenience caused. © 2020